Airway Management - Khan, Zahid Hussain (Springer eBooks, 2014)
This book integrates chapters on a variety of topics ranging from airway physiology to scenarios of a difficult airway, and reviews and management options in patients who are known to have a difficult airway such as the difficult pediatric airway, the difficult airway in obstetrics, and those suffering from obstructive sleep apnea. All the chapters are written by renowned contributors from all over the world with tremendous experience and expertise in the various fields. The probable overspill of the secretions into the lungs is a tangible fear and this aspect has been fully addressed in the chapters. The reviews presented herein describe difficult airway scenarios in a plethora of clinical settings that would help the anesthesiologists, emergency medicine specialists and the intensivists in taking steps in the right direction when posed with a challenging airway, thus ensuring safe anesthesia practice and patient care, which is our most cherished goal.